PWE-055 Health-related behaviours in young people with inflammatory bowel disease. (17th June 2017) - Brooks, AJ; Rowse, G; Peach, EJ; Ryder, AH; Lees, R; Narula, P; Corfe, BM; Norman, P; Lobo, AJ
Abstract : Introduction: Health-related behaviours in adolescence affect health at the time and into adulthood. Insufficient physical activity and obesity are determinants of premature mortality (1), with obesity resulting in low self-esteem and educational attainment (2). Young people (YP) with inflammatory bowel disease (IBD) describe difficulties with eating and exercise (3), but no data exists regarding rates of such behaviours. The aim of this study was to investigate health-related behaviours of YP with IBD. Method: YP aged 16–22 years with a confirmed diagnosis of IBD were recruited from paediatric and adult IBD centres. Participants completed The Youth Risk Behaviour Survey (YRBS) – adapted, along with demographic, disease and treatment related data. Results: 121 patients were studied (75 (62%) CD, 39 (32%) UC, 7 (6%) IBDU), median age 19 years (range 16–22 years). Four health behaviour groups were identified including; 1) Body weight: described as underweight in 26/119 (22%), overweight in 40/119 (34%) including 26/119 (22%) trying to lose/maintain weight in last month by fasting/use of medications in 10/118 (8%); 2) Healthy eating: 99/119 (83%) and 111/119 (93%) eating fruit or vegetables in last 7 days respectively and 26/97 (27%) consuming fizzy drinks > once/day. 3) Physical activity: 91/118 (77%) exercising for > 1 hour in last 7 days and of these 32/91 (35%) exercising on > 5 days, with 47/108 (44%) watching TV > 3 hours/day and 61/108 (56%) playing video games/browsing internet > 3 hours/day; 4) Health promotion: 98/118 (83%) taught about HIV/AIDS and 19/118 (16%) tested for HIV, 23/118 (19%) use SPF15+ sunscreen most of time and in last year 13/118 (11%) use tanning devices. Males were significantly more likely to try to gain weight (25/59 vs. 8/60) (p=0.0005), and females significantly more likely to try to lose weight (30/60 vs 10/59) (p=0.0002). Conclusion: Over half of YP with IBD report dissatisfaction with body weight, with an obesogenic lifestyle reported in many and behaviours related to an increased risk of skin cancer are observed. In order to maximise health, well-being and productivity in YP with IBD, screening for adverse health-related behaviours is needed with innovative individualised interventions delivered by IBD teams. References: . Stringhini S, et al. Lancet2017 . State of Child Health Report2017, Royal College of Paediatrics and Child Health . Daniel J. Gastroenterol Nurs2002 Disclosure of Interest: A. Brooks Conflict with: Crohn's and Colitis UK, G. Rowse: None Declared, E. Peach: None Declared, A. Ryder: None Declared, R. Lees: None Declared, P. Narula: None Declared, B. Corfe: None Declared, P. Norman: None Declared, A. Lobo Conflict with: Takeda Pharma, Abbvie, Vifor Pharma, Dr Falk and Shield Therapeutics., Conflict with: Takeda Pharma, Abbvie, Vifor Pharma, Dr Falk and Shield Therapeutics.